Evaluating the Suitability of Groundwater for Irrigation uses at Al-Salhubia Area, Al-Muthana Governorate, Southern Iraq - Al-Azawi , Ali A. Obeed; Al-Shamma'a , Ayser Mohammed (Iraqi Journal of Science, 2022)
Al-Salhubia, area is located within the arid region in southern Iraq. Although no surface water is available in this area, the groundwater is considered the basis in the area, it is available in both good quality and quantity. For that reason, it is of prime importance to examine water type in the unconfined aquifer to determine suitability of groundwater for irrigation purposes. The groundwater type in the studied area is Ca-Mg dominant SO4 facies according to Piper and Stiff diagrams. Based on SAR, Na%, RSC, EC, and PI, the groundwater quality in the study area is suitable for irrigation in general.